2013
DOI: 10.1016/j.jtcvs.2013.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic outcomes of segmentectomy compared with lobectomy for clinical stage IA lung adenocarcinoma: Propensity score–matched analysis in a multicenter study

Abstract: Segmentectomy is suitable for clinical stage IA lung adenocarcinoma, with survivals equivalent to those of standard lobectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(105 citation statements)
references
References 18 publications
4
99
1
1
Order By: Relevance
“…In this study, according to postoperative measurement, the tumors resected in the segmentectomy group had smaller diameters than those in the lobectomy group; similar findings have been reported by others both in China and other countries (18,19). Because this study was retrospective and there were no standardized guidelines for selecting the procedure, individual surgeons decided which patients would undergo anatomic segmentectomy, which may have skewed the results.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In this study, according to postoperative measurement, the tumors resected in the segmentectomy group had smaller diameters than those in the lobectomy group; similar findings have been reported by others both in China and other countries (18,19). Because this study was retrospective and there were no standardized guidelines for selecting the procedure, individual surgeons decided which patients would undergo anatomic segmentectomy, which may have skewed the results.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, only few inter-lobar fissures need to be incised to provide an adequate field of vision, the lung lobe structure and position do not change markedly, more of the tissue in the affected lung lobe can be left in situ, and the recruitment maneuver is unnecessary: unlike lobectomy, anatomic segmentectomy does not require a maneuver to recruit other lung lobes on the affected side to fill the residual cavity. Other studies (19,20) have reported that S-VATS anatomic segmentectomy is associated with a more rapid postoperative recovery.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Focal fibrosis [5] Follicular lymphocytic bronchiolitis [3] Inflammation, nonspecific [1] Mucoid plug [1] Hamartoma [1] Focal subpleural fibroelastosis [1] Amyloid nodule [1] Metastatic lung tumour (n=65)…”
Section: From Marking To Mappingmentioning
confidence: 99%
“…It is increasingly clear that segmentectomies provide comparable outcomes to lobectomies for earlystage lung cancers, particularly in those with ground-glass nodules (GGNs) (5,6). In contrast, a potential challenge…”
Section: Introductionmentioning
confidence: 99%